Comparison of bleeding risks among non-vitamin K antagonist oral anticoagulants using the Korea adverse event reporting system database. (September 2019) - Ko, Young-Jin; Kim, Seonji; Park, Kyounghoon; Kim, Minsuk; Yang, Bo Ram; Lee, Joongyub; Kim, Mi-Sook; Park, Byung-Joo
Background: In order to ensure safer use of non-vitamin K antagonist oral anticoagulants (NOACs), continuously detecting unexpected adverse drug reactions (ADRs) after market approval is necessary. Methods: We performed disproportionality analysis to evaluate association between ADRs and NOACs including apixaban, dabigatran, and rivaroxaban using data from the Korea Institute of Drug Safety and Risk Management–Korea Adverse Event Reporting System database (KIDS-KD) between 2012 and 2016. There was no significant signal other than bleeding when considering quantity, signal strength, seriousness, and causality. In order to evaluate the NOAC reports about bleeding, we selected 62 WHO-ART diagnostic codes associated with bleeding. Among the 26 codes that referred to major bleeding, 18 codes referred to gastrointestinal bleeding and 8 were referred to intracranial bleeding. We evaluated the significance of the signals using reporting odds ratios (RORs) adjusted for age and sex. Results: Treatments with apixaban, dabigatran, and rivaroxaban were associated with 1989, 1668, and 2960 adverse events, respectively. Any type of bleeding with apixaban, dabigatran, rivaroxaban, and warfarin was reported in 174 (8.8%), 209 (12.5%), 523 (17.8%), and 620 (9.5%) events, respectively. For any bleeding, adjusted RORs of apixaban, dabigatran, and rivaroxaban were 0.99 [95% confidence interval (CI): 0.83–1.17], 1.47 (95% CI: 1.25–1.75), and 2.48 (95% CI: 2.16–2.84), respectively. With respect to major bleeding, the adjusted RORs of apixaban, dabigatran, and rivaroxaban were 1.08 (95% CI: 0.82–1.41), 1.46 (95% CI: 1.10–1.90), and 1.82 (95% CI: 1.43–2.32), respectively. Conclusion: Rivaroxaban might have stronger association with bleeding than apixaban and dabigatran.